PEMBELAJARAN MEMBACA PEMAHAMAN MENGGUNAKAN MODEL SNOWBALL THROWING PADA SISWA KELAS V SEKOLAH DASAR - eva mulia agustin; Kamidjan Kamidjan; Ratih Asmarani (Wacana Didaktika, 2019)
Understanding reading skills are needed to achieve the goal so that students can more easily obtain information or content from reading. Based on the results of preliminary observations conducted by researchers in class V of Tampingmojo State Elementary School in Tembelang Jombang, it was shown that students' reading comprehension skills were still low. One way that teachers use to overcome students' problems in reading comprehension is using the Snowball Throwing model. This study aims to examine the application of the Snowball Throwing model to improve reading comprehension skills of fifth grade students of SD Tampingmojo Tembelang Elementary School. This type of research uses qualitative research with a descriptive approach. Subjects in this study were teachers and fifth grade students of SD Negeri Tampingmojo Tembelang. Data obtained by observation, interviews, tests, documentation and field notes. The results showed that the learning process of reading comprehension using the Snowball Throwing model was increasing and optimal. Evidenced from the student scores on pre-test that is 70,5% with enough categories, meeting post I that is 80,2% with good categories and meeting post II which is 86% with excellent categories. The conclusion this study is the application of the Snowball Throwing model able to improve reading comprehension of the fifth students of SD Tampingmojo Elementary School Tembelang Jombang. Keywords: reading comprehension, Snowball Throwing model. Abstrak: Keterampilan membaca pemahaman dibutuhkan siswa untuk lebih mudah mendapatkan informasi atau isi dari bacaan. Peneliti melakukan observasi awal yang menunjukkan bahwa keterampilan membaca pemahaman siswa pada kelas V SD Negeri Tampingmojo Tembelang Jombang masih rendah. Tujuan dari penelitian ini adalah untuk menelaah penerapan model Snowball Throwing dalam meningkatkan kemampuan membaca pemahaman siswa kelas V SD Negeri Tampingmojo Tembelang. Jenis penelitian ini menggunakan penelitian kualitatif dengan pendekatan kuantitatif dan kualitatif. Guru dan siswa kelas V SD Negeri Tampingmojo Tembelang Jombang adalah sebagai subjek dalam penelitian ini. Data diperoleh dengan teknik observasi, wawancara, tes, dokumentasi dan catatan lapangan. Hasil penelitian ini menunjukkan bahwa proses pembelajaran membaca pemahaman menggunakan model Snowball Throwing semakin meningkat dan optimal. Dibuktikan dari nilai siswa pada pre tes yaitu 70,5% kategori cukup, pos tes pertemuan I yaitu 80,2% dengan kategori baik dan pos tes pertemuan II yaitu 86% sangat baik. Kesimpulan penelitian ini adalah model Snowball Throwing mampu meningkatkan kemampuan membaca pemahaman siswa kelas V SD Negeri Tampingmojo Tembelang Jombang.